Measuring Vertical Integration in the Technology Sector: Indonesia, the US, and the EU in Unfair Competition - Anna Maria Tri Anggraini; Ahmad Sabirin; Maria Silvya Elisabeth Wangga; Sharda Abrianti; Serena Ortigosa Fernandez (Journal of Law and Legal Reform, 2024)
On several occasions, Indonesian competition authorities have attempted to apply Article 14 to adjudicate violations related to vertical integration practices; however, these attempts were invalidated at the objection and cassation levels. The criteria utilized include the concepts of unfair business competition and public harm, as these terms are instrumental in determining the impacts of violations concerning vertical integration. This research aims to examine the legal approaches employed by Indonesian competition authorities in addressing vertical integration, with a particular focus on the technology sector. The findings indicate that the criteria for assessing whether vertical integration constitutes a violation of unfair business competition vary among Indonesia, the United States, and the European Union. In Indonesia, the emphasis is on preventing the exclusion of access to essential raw materials or significant buyers, utilizing the Rule of Reason approach. In contrast, the U.S. evaluates public detriment by balancing fairness and competitive benefits, whereas the EU focuses on market dominance and its potential to reduce competition. Despite these variations, all three jurisdictions share a common objective of enhancing consumer welfare and promoting competitive market conditions, with specific regard to differing regulations on online sales restrictions.